Critical role of zeolites as H2S scavengers in argyrodite Li6PS5Cl solid electrolytes for all-solid-state batteries. Issue 32 (3rd August 2021) - Lee, Donggun; Park, Kern-Ho; Kim, So Yeun; Jung, Jae Yup; Lee, Wonrak; Kim, KyungSu; Jeong, Goojin; Yu, Ji-Sang; Choi, Jungkyu; Park, Min-Sik; Cho, Woosuk
Abstract : A composite electrode containing a zeolite (ZSM-5) embedded Li6 PS5 Cl solid electrolyte, where zeolite can act as a scavenger for both toxic H2 S gas and moisture is designed for realizing high-performance all-solid-state batteries (ASSBs) with improved cycle performance. Abstract : All-solid-state batteries (ASSBs) with inorganic solid electrolytes (SEs) have received much attention as future energy storage systems owing to their high energy densities and excellent safety. Sulfide-based SEs are considered promising because they exhibit greater ionic conductivities and mechanical softness than oxide-based SEs. In particular, argyrodite-type Li6 PS5 Cl with a high ionic conductivity of 3.0 × 10 −3 S cm −1 offers new possibilities for realizing high-performance ASSBs. However, contact with moisture results in the evolution of H2 S from Li6 PS5 Cl, which has hindered the scalable fabrication and practical application of Li6 PS5 Cl. To avoid this issue, we propose incorporating a zeolite, which can act as a scavenger for both toxic H2 S gas and moisture, as a functional additive in Li6 PS5 Cl. We demonstrate that zeolite-embedded Li6 PS5 Cl exhibits greatly improved chemical stability and reduced H2 S evolution upon storage in humid air (RH 50%), leading to a noticeable improvement in the cycle performance of ASSBs. This approach could resolve the technical issues associated with sulfide-based SEs toward commercial-scale implementation.